2011
DOI: 10.1002/jts.20616
|View full text |Cite
|
Sign up to set email alerts
|

Female sexual self‐schema after interpersonal trauma: Relationship to psychiatric and cognitive functioning in a clinical treatment‐seeking sample

Abstract: This study assessed the relationship between sexual self-schema and posttraumatic functioning in a clinical sample of 112 female sexual assault survivors. Contrary to hypotheses, posttraumatic stress disorder and depressive symptom severity were unrelated to the valence of sexual self-schema. Yet, negative posttraumatic cognitions were related to sexual self-schemas. Specifically, less positive self-views were associated with more negative schema (r = -.35). In a multivariate analysis, the measure of negative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Constructivist Self-Development Theory (CSDT) illuminates how traumatic events like exposure to violence during childhood can produce both negative and, at times, positive impacts for the affected individual (Blain et al 2011;Pearlman 1997;Wright et al 2009) Consistent with Children's Health Equity Solutions Center's (CHESC) "individual differences" theme, CSDT views differences in children's beliefs, and cognitive schemas about violence alter how exposure to violence manifests in their adult lives. Likewise, paralleling the CHESC's "context matters" theme, CSDT posits that both socioeconomic and temporal contexts of violence exacerbate or minimize the downstream consequences of violence exposure.…”
Section: Constructivist Self-development Theorymentioning
confidence: 99%
“…Constructivist Self-Development Theory (CSDT) illuminates how traumatic events like exposure to violence during childhood can produce both negative and, at times, positive impacts for the affected individual (Blain et al 2011;Pearlman 1997;Wright et al 2009) Consistent with Children's Health Equity Solutions Center's (CHESC) "individual differences" theme, CSDT views differences in children's beliefs, and cognitive schemas about violence alter how exposure to violence manifests in their adult lives. Likewise, paralleling the CHESC's "context matters" theme, CSDT posits that both socioeconomic and temporal contexts of violence exacerbate or minimize the downstream consequences of violence exposure.…”
Section: Constructivist Self-development Theorymentioning
confidence: 99%
“…Previous studies have highlighted the potential relevance of cognitive factors in the co-association between PTSS and sexual dysfunctions (Blain et al, 2011). Individuals with PTSS often experience negative self-referential cognitions (e.g., “The trauma has changed me forever”) or thoughts of self-blame (“The trauma happened because of how I acted”; Foa et al, 1999), which can increase negative self-referential affect, such as shame or guilt (Beck et al, 2011; Leskela et al, 2002).…”
mentioning
confidence: 99%
“…Moreover, few studies to date have examined the association between PTSS and sexual self-schemas following sexual violence exposure. Blain et al (2011) examined the sexual self-schemas of women with histories of adult sexual trauma and found that PTSD-related negative self-referential cognitions about the self were significantly associated with more negative sexual self-schemas. Thus, it is possible that components of PTSD may alter a survivor’s sexual self-schema, which may in turn, reduce sexual functioning or satisfaction.…”
mentioning
confidence: 99%